The effectiveness of Interpersonal Psychotherapy-Adolescent Skills Training for adolescents with depression: a systematic review and meta-analysis - Zheng, Kewei; Xu, Huimin; Qu, Chunhui; Sun, Xianghong; Xu, Na; Sun, Ping (Frontiers in Psychiatry, 2023)
Background Interpersonal Psychotherapy-Adolescent Skills Training (IPT-AST) is a standardized depression prevention program for adolescents conducted in campus settings. The purpose of this review is to examine the randomized controlled trials of IPT-AST for the prevention of adolescent depression in the past 20 years. Methods A systematic search of relevant electronic databases (PubMed, WOS, Embase, PsycINFO, the Cochrane Library, CNKI and WANFANG DATA) and study reference lists was conducted. Any study investigating the effectiveness of IPT-AST in 12- to 20-year-olds with depressive symptoms was eligible. Synthesis was via narrative summary and meta-analysis. Results A total of 6 studies met the inclusion criteria. Meta-analysis results showed a remarkable improvement in patients’ depressive symptoms after IPT-AST intervention (WMD = −5.05, 95% CI = −8.11 to −1.98, p < 0.05, I2 = 77%). Six month follow-up data showed that the intervention outcomes of IPT-AST remained significant (WMD = −3.09, 95% CI: −5.23 to −0.94, p < 0.05, I2 = 57%). Conclusion This meta-analysis showed that IPT-AST was effective in adolescents with depressive symptoms at post-prevention and at 6-month follow-up. However, these conclusions are cautious, as they are based on a small number of studies and the presence of author duplication. Future studies should use multi-center, large-sample randomized controlled trials to evaluate the efficacy of IPT-AST for preventing depression in adolescents. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier CRD42023393047.